1999
DOI: 10.1515/bc.1999.138
|View full text |Cite
|
Sign up to set email alerts
|

Fluorometric Microassays for the Determination of Cathepsin L and Cathepsin S Activities in Tissue Extracts

Abstract: We established a continuous semi-microassay, and for large-scale studies both a stopped and a continuous microtiter plate assay for the fluorometric determination of cathepsin L and cathepsin S activities in body fluids, tissues or cell extracts in the presence of cathepsin B. For the detection of enzymatic activities we used the synthetic substrate Z-Phe-Arg-AMC, and for discrimination between cathepsin L, S and cathepsin B the specific inhibitor CA-074 for blocking interfering cathepsin B activities was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…showed that the replacement of a 50 mmol/L citrate assay buffer by a 50 mmol/L MES buffer led to the total abolition of the inhibition of cathepsins L, S, and K by the rCatKPP (9). In these experiments, the fluorimetric assays were done in a 100 mmol/L sodium acetate buffer (pH 5.5), as has been published previously (20,21), and is suitable for use with the each of the cathepsin L -like cysteine cathepsins.…”
Section: Expression and Purification Of Rcatsppmentioning
confidence: 80%
“…showed that the replacement of a 50 mmol/L citrate assay buffer by a 50 mmol/L MES buffer led to the total abolition of the inhibition of cathepsins L, S, and K by the rCatKPP (9). In these experiments, the fluorimetric assays were done in a 100 mmol/L sodium acetate buffer (pH 5.5), as has been published previously (20,21), and is suitable for use with the each of the cathepsin L -like cysteine cathepsins.…”
Section: Expression and Purification Of Rcatsppmentioning
confidence: 80%
“…Assays used 20 M benzyloxycarbonyl-L-phenylalanyl-L-arginine-7-amido-4-methylcoumarin (ZPhe-Arg-AMC; Anaspec) at pH 7.5 in 100 mM Na-Acetate with 2.5 mM EDTA, 0.01% Triton X-100, and 2.5 mM DTT in a microtiter plate [24] with ~0.3 g of extract at 37 °C. The amount of product was determined by excitation at 355 nm and emission at 460 nm using a kinetic reading for a microtiter plate and comparison with 7-amino-4-methylcoumarin standards from Anaspec.…”
Section: Methodsmentioning
confidence: 99%
“…Cathepsin L -type activity in cell lysates was measured using the previously described method 22 with modifications. Briefly, an aliquot of 15 g of total protein diluted in 100 L of double distilled water was incubated in 870 L of 0.34 M sodium acetate buffer, pH 5.5, containing 2 mM EDTA -Na 2 ( Sigma).…”
Section: Cathepsin L -Type Activity Assaymentioning
confidence: 99%